FACTORS AFFECTING POST-OPERATIVE PAIN AFTER DOPPLER GUIDED HEMORRHOID ARTERY LIGATION AND RECTO-ANAL REPAIR (DGHAL-RAR) OF INTERNAL HEMORRHOID - Sigit Adi Prasetyo; Ignatius Riwanto (Media Medika Muda, 2016)
Background: DGHAL-RAR is new modality for grade II-IV internal hemorrhoid treatment. It is developed to reduce post-operative pain that mostly found in traditional hemorrhoidectomy even in Stappler hemorrhoidopexy. However, in clinical practice some patients are complaint of moderate until severe pain. This study is intended to know factors affecting the post-operative pain after DGHAL-RAR of internal hemorrhoid.Methods: A series of 61 grade II-IV internal hemorrhoid patients, underwent DGHAL-RAR in St Elizabeth Hospital, Semarang Indonesia, period of August 2012 – March 2014 were analyzed prospectively. Age, sex, grade, removing of thrombus  either internal or external, anal fissure, removing of hypertrophic anal papilla, removing skin tag, anal laceration due to procedure, were analyzed to know it relation with post operative pain in 24 hours, 48 hours and 7 days post-operatively. VAS for pain (0–10) were used to assess the degree of pain. Mann-Whitney method was used for univariate analysis, while Kruskal-Wallis and Median method were used for multivariate analysis.Results: After multivariate analysis variables that significantly influence post operative pain on 24 hours were removing of internal thrombosis, removing of anal papilla hypertrophy and anal laceration, on 48 hours were removing of external thrombosis, removing of anal papilla hypertrophy and anal laceration and  on 7 days were the same with on 24 hours.Conclusion: Factors that affecting post-operative pain after DGHAL-RAR  for grade II-IV internal hemorrhoid were removing of both internal and external thrombosis, removing of anal papilla hypertrophy and anal laceration due to DGHAL-RAR procedure. Keywords: Internal hemorrhoid, Hemorrhoid artery ligation and recto-anal repair, thrombosis, anal papilla hypertrophy, anal laceration.